The Single Currency's Effects on Eurozone Sectoral Trade: Winners and Losers? - Claudio Vicarelli; Roberta De Santis; Sergio De Nardis (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
In this paper we study the effect of the single currency across industries for euro area members. This analysis may help to shed light on the main factors influencing the euro effect on trade flows. We intend to verify whether these factors are specific to individual sectors and/or countries or common to the entire euro area. We use a dynamic specification of an augmented gravity equation. Following the most recent econometric literature, we apply the ?System GMM? dynamic panel data estimator of Blundell and Bond to avoid inconsistency and biases in the estimates, and introduce controls for heterogeneity. Aggregate sector results average out country-level behaviours that, on their turn, are affected by different (unobserved) responses of firms, endowed with diverse production costs, to the enhancing and dampening impacts due to the euro. Due to this reason, the cancelling out at aggregate level of heterogenous behaviours induces an aggregation bias. So it is not surprising that when moving from sector to sector/country analysis the picture becomes much more variegated, with the emergence of a whole range of winners and lossers among industries in the different nation. Our empirical results are in line with theoretical framework we assumed as reference that considers the possibility of both stimulative and dampening effects coming from trade integration and points out the fact that sector exports impacts are the aggregation results of firm-level heterogenous behaviours.
Keywords: C33; F4; F15; F14; F33; 330; International trade; currency unions; gravity models; dynamic panel data; Blundell-Bond estimates; Europäische Wirtschafts- und Währungsunion; Euro; Industriegüteraußenhandel; Außenhandelseffekt; Gravitationsmodell; EU-Staaten